The Orientation in Learning English (A Study of the Causal Factors of Students’ Integrative and Instrumental Motivation) - Nur Ayu Puspita Sari Sukri; Nasmilah Nasmilah; Ria Rosdiana Jubhari (ELS Journal on Interdisciplinary Studies in Humanities, 2021)
This study aims to investigate the students’ motivational orientations in learning English. The method of this research is a quantitative method and a questionnaire is used to collect the data. The result from this research indicates that there are differences in the level of motivation possessed by female and male students. Females tend to learn English with the aim of understanding English in terms of literacy and culture. Meanwhile, males learn English because they want to get good privileges such as having broad insight, getting a good job, and social status. Males have a high level of instrumental motivational orientation with a total percentage of 72.50% while females have 67.50%. Besides that females achieve a high integrative level with a percentage of 92.50% and males reached 80%. It can be concluded that males and females have different motivational orientations.